2023
DOI: 10.2147/ccid.s411636
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical Characteristics in Overweight/Obese and Normal Weight Patients with Psoriasis Vulgaris: A Bicentric Retrospective Observational Study

Abstract: Background Psoriasis is a chronic, inflammatory skin disease that is often accompanied by multiple comorbidities. Obesity is considered an independent risk factor for the development of psoriasis. However, most of the related data are derived from epidemiological studies conducted in the United States of America and Europe. This study aimed to compare the clinical characteristics of patients with psoriasis who are overweight/obese and patients with psoriasis with normal weight in China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…These findings suggest that lean-type MASLD might cause less synergistic damage to plaque psoriasis than typical MASLD, pointing to weight management as a potential comprehensive strategy for treating patients with both plaque psoriasis and MASLD. A bicenter retrospective study published in 2023 also supports our perspective on the importance of weight management in psoriasis patients ( 50 ).…”
Section: Discussionmentioning
confidence: 54%
“…These findings suggest that lean-type MASLD might cause less synergistic damage to plaque psoriasis than typical MASLD, pointing to weight management as a potential comprehensive strategy for treating patients with both plaque psoriasis and MASLD. A bicenter retrospective study published in 2023 also supports our perspective on the importance of weight management in psoriasis patients ( 50 ).…”
Section: Discussionmentioning
confidence: 54%
“…An observational study conducted by Czarnecka et al (12) found no significant association between normal BMI (<25 kg/m 2 ) and psoriasis severity (r = -0.001. and p = 0.917), but found a statistically significant association between abnormal BMI (≥ 25 kg/m 2 ) and PASI score (r = 0.23, and p = 0.016). Li et al (24) observed that overweight or obese subjects with psoriasis had significantly more severe psoriatic lesions and metabolic comorbidities. Therefore the study results on the correlation of BMI with psoriasis severity are still inconsistent.…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory milieu in PsA is attributed to adipose tissue, whose dysregulation maintains chronic low-grade systemic inflammation [ 14 ]. Therefore, in order to reduce the risk of developing metabolic complications, it is mandatory for Ps and PsA patients to control their BMI primarily through losing weight [ 15 ]. The most accessible strategy for lowering BMI and reducing adipose tissue in Ps patients is a low-calorie diet.…”
Section: Psoriatic Patients and Obesitymentioning
confidence: 99%